2010
DOI: 10.1007/s10979-009-9208-6
|View full text |Cite
|
Sign up to set email alerts
|

Why emotions matter: Expectancy violation and affective response mediate the emotional victim effect.

Abstract: The mechanisms behind the 'emotional victim effect' (i.e., that the emotionality of a rape victim's demeanor affects perceived credibility) are relatively unexplored. In this article, a previously neglected mechanism--observers' affective response to the victim--is proposed as an alternative to the traditional expectancy-violation account. The emotional victim effect was replicated in an experiment with a sample of police trainees (N = 189), and cognitive load was found to increase the magnitude of the effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(175 citation statements)
references
References 49 publications
11
157
4
3
Order By: Relevance
“…Based on the data above, it appears that mock jurors transfer their belief in who is telling the truth based on who is showing more emotion and whether this fits with expectations (e.g., Ask & Landström, 2010;Calhoun, Cann, Selby, & Magee, 1981). In general, research on both true and false allegations has reported that high levels of emotional expression (both in terms of demeanor and content of a claim) are more often associated with a genuine claims of criminal events (e.g., Kaufmann et al, 2003;Peace, Brower, & Shudra, 2012;Peace, Porter, et al, 2012;Wessel et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Based on the data above, it appears that mock jurors transfer their belief in who is telling the truth based on who is showing more emotion and whether this fits with expectations (e.g., Ask & Landström, 2010;Calhoun, Cann, Selby, & Magee, 1981). In general, research on both true and false allegations has reported that high levels of emotional expression (both in terms of demeanor and content of a claim) are more often associated with a genuine claims of criminal events (e.g., Kaufmann et al, 2003;Peace, Brower, & Shudra, 2012;Peace, Porter, et al, 2012;Wessel et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, other studies have found support for an emotive truth bias, where emotional claims and stories are more likely to be believed and perceived as truthful relative to non-emotional claims (e.g., Peace, Porter, & Almon, 2012;Peace & Sinclair, 2012). Also relevant to consider is whether the emotional display of a victim is consistent with or in violation of expected norms, also called expectancy violation (i.e., a violation of a predicted pattern in behavior or emotions; Ask & Landström, 2010;Burgoon, 1993). When an expectancy violation is made, attention is drawn away from the content of the situation and toward the individual in violation, and the possible reasons for that violation (Burgoon, 1993).…”
Section: The Role Of Emotionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, Ask and Landstrom (2010) established that, in relation to the emotional expressiveness of a rape victim, some people have expectations about the emotions a rape victim will display when reporting their rape to the police. For those participants who held these expectations, the emotionally expressive victim was assessed as more credible compared to the non-emotionally expressive victim (see also Hackett, Day, & Mohr, 2008;Klippenstein & Schuller, 2012).…”
mentioning
confidence: 99%